Programa Agro Legal: a interação do Ministério Público de Minas Gerais com os Poderes Executivo e Legislativo na constituição de uma política municipal de agricultura familiar - Costa, Andreia Teixeira (Universidade do Vale do Rio dos Sinos, 2023)
The present work tried to understand the conditions for the implementation of the Agro Legal Program, which was instituted by Municipal Law n. a Direct Action of Unconstitutionality – ADU specific to article 28 of the Municipal Organic Law and based on a complaint published on a news blog on the internet, which reported the misuse and storage of public assets. The MPMG sought explanations from the Executive and Legislative Powers about decision-making and transparency in providing access to public equipment and machinery for small farmers established in settlements in the municipality of Unaí/MG. The present study problematized the reasons that led the Public Ministry of Minas Gerais to propose the ADI, and the initiative to constitute the Agro Legal Program. The research went through an exploratory moment of gathering information through interviews with the Department of Agriculture, the City Hall of Unaí, the Chamber of Councillors, the Public Ministry of Unaí and the citizen responsible for the complaint that occurred in 2012. The methodology used presents an approach qualitative, exploratory type, deductive method, use of primary and secondary sources, the theoretical investigation technique was the bibliographic and the empirical investigation technique was the case study, the instrument for data generation was the semi-structured interview, the participating subjects of the research are linked to the Public Administration of the municipality of Unaí/MG, in addition to the President of the Legislative Chamber, and the Prosecutor of the Public Ministry of Minas Gerais and the data were analyzed through content analysis. Finally, the final considerations show that the Agro Legal Program was the result of interference by the MPMG, as a way of regulating what was already being implemented, with the assignment of agricultural machinery and municipal public servants to local family farmers, in order to try to remedy the improper use of said machinery for the benefit of individuals.
Keywords: Programa Agro Legal; Ministério Público; ADI; Agro Legal Program; Public ministry; ADU; ACCNPQ::Ciências Humanas::Sociologia